2020
DOI: 10.1109/access.2020.2989860
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Secure Millimeter Wave NOMA Communications in Cognitive Radio Networks

Abstract: In this paper, an easy analysis framework is developed to evaluate the reliability and security of the secondary receivers (SU-Rxs) in millimeter wave (mmWave) non-orthogonal multiple access (NOMA) aided cognitive radio (CR) networks, where secondary transmitters (SU-Txs) transmit confidential messages to SU-Rxs belonging to different regions under the interference temperature constraint of the primary receiver (PU-Rx). Considering that randomly located eavesdroppers and primary user may be in the signal beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…The impact of this quantization errors on the performance of existing algorithms must be evaluated and new improved ones must be proposed if necessary. • Cognitive radio: One solution to increase the spectral efficiency and to reply to the increasing traffic demand is to combine cognitive radio and mmWave communications, this perspective had been studied in several recent research works [207]- [209]. In this context, the problem of joint channel estimation and spectrum sensing for the secondary and the primary users must be further investigated.…”
Section: Discussion and Open Directions Of Researchmentioning
confidence: 99%
“…The impact of this quantization errors on the performance of existing algorithms must be evaluated and new improved ones must be proposed if necessary. • Cognitive radio: One solution to increase the spectral efficiency and to reply to the increasing traffic demand is to combine cognitive radio and mmWave communications, this perspective had been studied in several recent research works [207]- [209]. In this context, the problem of joint channel estimation and spectrum sensing for the secondary and the primary users must be further investigated.…”
Section: Discussion and Open Directions Of Researchmentioning
confidence: 99%
“…The block Nakagami-m fading is adopted to model the channels in the wireless networks, which is a generalized model and can be degraded to Rayleigh fading and Rician fading by choosing different fading parameters [34]. The channel between the transmitter and relay is denoted as h R with mean Ω R and fading parameter m R .…”
Section: Network Model and Transmission Schemes A Network Modelmentioning
confidence: 99%
“…To address some of the 5G challenges including spectrum efficiency and massive connectivity, it is necessary to study the combination of NOMA with CR networks while maintaining reliable transmission of primary and secondary users. In various circumstances of the underlay CR-NOMA developed in [7][8][9][10], a superimposed signal is sent by the secondary transmitter to the secondary NOMA destination users. The authors concluded that if the PA factors and target rates are accurately chosen, the performance of NOMA users can be enhanced.…”
Section: Introductionmentioning
confidence: 99%